2017
DOI: 10.1111/bjd.15235
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of moderate-to-severe atopic eczema in adults within the U.K.: results of a national survey of dermatologists

Abstract: SummaryBackgroundLittle is known about U.K. dermatologists' treatment approaches towards adult patients with recalcitrant moderate‐to‐severe atopic eczema.ObjectivesWe wanted to learn about (i) treatment approaches used for this disease in the U.K.; (ii) factors that influence treatment decisions and (iii) perceived gaps in evidence on treatment safety and efficacy, and priorities for future trials.MethodsWe conducted an online survey of consultant‐level dermatologists in the U.K.ResultsSixty‐one respondents f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 26 publications
2
46
0
4
Order By: Relevance
“…Baseline data from a German registry of moderate‐to‐severe AD revealed that 13% of participants had been on systemic CS in the 3 months prior to enrollment, and in another German study, 10% of patients with AD had used systemic CS over 2 years . In a survey of 61 U.K. consultant dermatologists, 42% listed systemic CS as their first‐line systemic agent for adult moderate‐to‐severe AD . In surveys of European and North American paediatric dermatologists, oral CS were the first‐line systemic agents for severe paediatric AD for 31% and 5% of respondents, respectively …”
Section: Approach To Systemic Corticosteroid (Cs) Use In Atopic Dermamentioning
confidence: 99%
“…Baseline data from a German registry of moderate‐to‐severe AD revealed that 13% of participants had been on systemic CS in the 3 months prior to enrollment, and in another German study, 10% of patients with AD had used systemic CS over 2 years . In a survey of 61 U.K. consultant dermatologists, 42% listed systemic CS as their first‐line systemic agent for adult moderate‐to‐severe AD . In surveys of European and North American paediatric dermatologists, oral CS were the first‐line systemic agents for severe paediatric AD for 31% and 5% of respondents, respectively …”
Section: Approach To Systemic Corticosteroid (Cs) Use In Atopic Dermamentioning
confidence: 99%
“…In line with the concept of pharmacogenetic dosing, almost 95% of respondents from our 2013 survey agreed/strongly agreed that TPMT level at baseline should guide choice of initial dose. These data are consistent with an earlier survey of UK consultant which showed a high level of uptake of TPMT enzyme‐level testing by dermatologists (94%), compared with gastroenterologists (60%) and rheumatologists (47%), prior to prescribing azathioprine …”
Section: Pharmacogenetic Dosimetrymentioning
confidence: 60%
“…The evidence from this study and a placebo‐controlled cross over trial of azathioprine, also conducted in the UK, has underpinned recommendations in UK and European guidelines on disease treatment, and azathioprine is now in widespread use in the UK. For example, evidence from a 2013 survey of UK dermatologists conducted through the UK Translational Research Network in Dermatology (UK TREND) and the UK Dermatology Clinical Trials Network (UK DCTN), indicated that azathioprine has been widely adopted in the UK as a treatment of refractory atopic eczema . Systemic therapy was the most popular second‐line treatment option, chosen by 49% of respondents, and it was also the second most popular first‐line treatment option (after phototherapy), chosen by 36% of respondents.…”
Section: Evidence‐based Treatments For Atopic Eczemamentioning
confidence: 99%
“…As shown, survey studies showed great ability to recruit a high number of participants for dermatology studies in a manner bypassing geographical borders. In contrast, non‐web‐based surveys included significantly fewer participants on average …”
Section: Applications In Dermatologymentioning
confidence: 98%